Ayurvedic Management Of Oral Submucous Fibrosis -A Conceptual Study - Nayak, Ajay; Fiaz, Shamsa; bhatnagar, Sharad (International Research Journal of Ayurveda & Yoga, 2021)
Oral submucous fibrosis (OSF) is a chronic disease of the oral cavity characterized by abnormal collagen deposition and progressive fibrosis of the submucosal tissue. The prevalence rate of OSF was 6.3 % and gutakha chewing is the most common habit was present in OSF patients. Symptoms include ulceration, burning sensation, submucous fibrosis, restricted mouth opening and xerostomia. In Ayurveda oral submucous fibrosis is correlate with Sarvasara mukhatoga (Diseases of Oral cavity) described in Bruhatrayi. Betelnut, tobacco, lime, chilies etc. act like irritants and can cause damage to oral mucosa. Treatment including Pittashamaka Yoga and gandush (Oil pulling), nasya (Nasal medication), pratisarana (rubbing) etc. can be done in OSF patients. In present conceptual study we are highlighting the management of oral submucous fibrosis.